2021
DOI: 10.3390/ijerph18136987
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory Health Effects of Wildfire Smoke during Summer of 2018 in the Jämtland Härjedalen Region, Sweden

Abstract: During the summer of 2018 Sweden experienced a high occurrence of wildfires, most intense in the low-densely populated Jämtland Härjedalen region. The aim of this study was to investigate any short-term respiratory health effects due to deteriorated air quality generated by the smoke from wildfires. For each municipality in the region Jämtland Härjedalen, daily population-weighted concentrations of fine particulate matter (PM2.5) were calculated through the application of the MATCH chemistry transport model. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…2021;18:6987. [ 31 ] Sweden, 2018 wildfire events in Jamtland Harjedalen region Modeled WFS PM 2.5 exposures using MATCH model (complex meteorological and atmospheric chemical data) Clinic visits RR 1.68 (1.09, 2.57) for “smoke days” (daily maximum 1-h mean PM 2.5 > 20 μg/m 3 ) Malig BJ, et al Sci Total Environ. 2021;787:147,507 [ 32 ] San Francisco Bay area, Oct. 2017 wildfires County-level monitoring avg PM 2.5 during wildfire period compared to adjacent periods ED visits and hospital admissions ED asthma visits: RR 1.46 (1.38, 1.55) per 23 μg/m 3 ↑ in PM 2.5 during fire period, vs 0.77 (0.55, 1.08) in non-fire period Hahn MB, et al Geohealth.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2021;18:6987. [ 31 ] Sweden, 2018 wildfire events in Jamtland Harjedalen region Modeled WFS PM 2.5 exposures using MATCH model (complex meteorological and atmospheric chemical data) Clinic visits RR 1.68 (1.09, 2.57) for “smoke days” (daily maximum 1-h mean PM 2.5 > 20 μg/m 3 ) Malig BJ, et al Sci Total Environ. 2021;787:147,507 [ 32 ] San Francisco Bay area, Oct. 2017 wildfires County-level monitoring avg PM 2.5 during wildfire period compared to adjacent periods ED visits and hospital admissions ED asthma visits: RR 1.46 (1.38, 1.55) per 23 μg/m 3 ↑ in PM 2.5 during fire period, vs 0.77 (0.55, 1.08) in non-fire period Hahn MB, et al Geohealth.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have been published recently assessing a specific link between WFS and rhinitis or allergy symptoms, but with mixed results. Among the previously discussed asthma epidemiological studies, several included an assessment of the association between WFS and acute upper respiratory illnesses (URI), with some showing no significant WFS effect [ 25 , 31 ], one showing a positive association with RR 1.77 [ 23 ••], and one showing less impact of WFS compared to non-wildfire PM 2.5 on URI risk [ 32 ]. Fadadu et al [ 48 ] found a RR of 1.49 (1.07, 2.07) for children and 1.15 (1.02, 1.31) for adults for clinic visits for atopic dermatitis symptoms, during exposure to WFS from the 2018 Camp Fire in the San Francisco area.…”
Section: Introductionmentioning
confidence: 99%
“…With the everchanging and inevitable anthropogenic climate change, aging population and limited healthcare budget, the study of wildfires' impact on senior health is significant to the agendasetting of provincial policy and the sustainable development of national healthcare. [3][4][5][6][7] The City of Toronto and its subordinate municipalities as the most densely populated area became the most suitable place to research the impact and the relationship. The main objective of the research study on the impact of wildfire on Toronto's senior population is to comprehensively assess the cause, health risks and consequences faced by seniors during wildfire events, with a focus on how these events can strain healthcare infrastructure.…”
Section: Introductionmentioning
confidence: 99%
“…During the summer of 2018, the episodes of wildfire smoke were most intense in the sparsely populated region of Jämtland Härjedalen. Our previous study aimed to investigate the short-term respiratory health effects resulting from changes in the composition of the atmosphere due to emissions of pollutants from biomass burning [16]. Using the MATCH chemistry transport model, we calculated daily population-weighted concentrations of PM 2.5 for each municipality in the Jämtland Härjedalen region.…”
Section: Introductionmentioning
confidence: 99%